2022
DOI: 10.2478/revecp-2022-0010
|View full text |Cite
|
Sign up to set email alerts
|

Best proxy to determine firm performance using financial ratios: A CHAID approach

Abstract: The main purpose of this study is to investigate the best predictor of firm performance among different proxies. A sample of 287 Czech firms was taken from automobile, construction, and manufacturing sectors. Panel data of the firms was acquired from the Albertina database for the time period from 2016 to 2020. Three different proxies of firm performance, return of assets (RoA), return of equity (RoE), and return of capital employed (RoCE) were used as dependent variables. Including three proxies of firm’s per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…Table 2 shows the description of the eleven variables used in this paper, considering three reference domains: profitability, productivity, and size (Piotroski 2000;Kuncová et al 2016;Olawale et al 2017). For each variable, a series of information is provided: the direction of the indicator indicates the existence of a direct relationship (indicated with a "+" sign) or an inverse relationship with the composite index of performance (Pekuri et al 2012;Delen et al 2013;Krekel et al 2019;Nikhat et al 2014;Yousaf and Dey 2022). The years available, 2016,2017,2018,2019,2020, identify the period covered by the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Table 2 shows the description of the eleven variables used in this paper, considering three reference domains: profitability, productivity, and size (Piotroski 2000;Kuncová et al 2016;Olawale et al 2017). For each variable, a series of information is provided: the direction of the indicator indicates the existence of a direct relationship (indicated with a "+" sign) or an inverse relationship with the composite index of performance (Pekuri et al 2012;Delen et al 2013;Krekel et al 2019;Nikhat et al 2014;Yousaf and Dey 2022). The years available, 2016,2017,2018,2019,2020, identify the period covered by the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The same proxies are also employed by several authors in previous literature to measure firm profitability (Niazi et al, 2023;Jaworski and Czerwonka, 2022;. A study by Yousaf and Dey (2022) revealed that ROA is the best proxy to measure firm performance after analyzing 297 Czech firms' data from three sectors. However, ROA and ROE are the most common proxies used in the previous literature (Dženopoljac et al, 2023;Habib and Dalwai, 2023;Kayakus et al, 2023;Nawaz and Ohlrogge, 2022;Olohunlana et al, 2022;Kayani et al, 2020;Ahmed and Bhuyan, 2020;Samo and Murad, 2019).…”
Section: Firm Performancementioning
confidence: 98%
“…Existen además, sinnúmero de publicaciones que han servido de guía académica y empresarial, para desarrollar informes de diagnóstico y análisis de la situación financiera de las empresas (Eniola y Entebang, 2017), quienes plantean nuevas estrategias de análisis, comenzando por un diagnóstico financiero, estrategia que facilita identificar la rotación de los recursos, a partir de información relevante que provee indicadores relacionados con los inductores de valor de la empresa, como son la rentabilidad y el flujo de caja (Yousaf y Dey, 2022).…”
Section: La Gestión De La Información Financiera En Las Empresasunclassified